Configuration optimization of drilled shafts supporting bridge structures: Three case studies - Suarez Chacon, V. (2017)
A common approach to estimating the point of fixity is to utilize the results of a single pile lateral analysis. Although no universal agreement exists as to the definition of the location of the point of fixity, it is generally accepted that its location will affect the computed stresses and displacements of a bridge structure. This study summarizes a method to determine a cantilever s equivalent length of drilled shaft foundation elements supporting a bridge. Results from an equivalent frame model are compared to those for bents modeled using the finite element method and nonlinear soil models for three bridges in North Carolina. Results indicated that the equivalent frame model provides responses that are comparable to those obtained from more rigorous finite element analyses. The study presents the results of the optimization of the support system by reducing the number, or size, of the shafts while maintaining an acceptable level of safety. © 2012 American Society of Civil Engineers.